Imunofenótipo molecular de carcinomas mamários caninos e sua relação com fatores de prognóstico e sobrevida - Soares, Nicolle Pereira (2019)
Neoplasias are the most common affections in dogs, and the spontaneous mammary tumors are the most frequent in female bitches. More than 50% of the cases are malignant and it represent a heterogeneity disease group with variable morphology and biological behavior. Molecular expression of estrogen receptors (ER) and progesterone receptors (PR) are considered prognostic factors, and ER expression is essential for determination of molecular classification. Another molecular marker frequently evaluated in human breast cancer is type 2 human epidermal growth factor (HER2). 84 bitches were included in this study. The radiographic and ultrasound examination were performed in orden to verify metastases in lung and nodal metastases. The surgical excision was a treatment for the mammary tumor (total or bilateral unilateral mastectomy). Samples of mammary neoplasms were evaluated for histological type and the expression of ER, PR e HER2 by immunohistochemistry. Evaluation of total overall survival (OS), disease-free interval (DFS) and time to tumor development in remaining breast (TDTMR) was performed. ST was defined as time after mastectomy up to the date of death; the DFS was the time after mastectomy until the development of recurrence or metastasis, and the TDTMR was determined as the time after mastectomy until the appearance of tumor in the remaining mammary gland. In the bitch, it is often expressed in malignant mammary carcinoma and correlates with nuclear pleomorphism, high histological grade and mitotic index, as well as lower survival. Absence of ER, PR and HER2 expression characterizes the triple negative phenotype. In women, this phenotype is related to aggressive tumor histology, poor prognosis, presence of metastases and recurrences. In bitch, they also present aggressive behavior, poor prognosis and reduction of survival. The objective of this study was to verify the expression of ER and the frequency of triple negative phenotype in canine mammary carcinomas (CMC) and correlate them with clinicopathological characteristics, overall survival (OS), disease-free interval and tumor development time in the breast remaining in bitches. In this study, the expression of estrogen was identified in 30.95% of canine mammary carcinomas, old-aged bitches, complex histological type grade II. Age was identified as a prognostic factor in canine mammary tumors and neoplasms of lower histological grade expressed more RE. The isolated evaluation of this molecular marker was not a good prognostic factor when considering total survival (483.42 ± 319.17 days) disease-free time (234.45 ± 241.05 days) and the time of tumor development in remaining mammary gland (279.68 ± 317.75 days). Furthermore, 21.43% of CMC were identified as a triple negative phenotype. None of the clinicopathological parameters evaluated (type and histological grade, clinical stages, stromal invasiveness, age, size and tumor location) differed significantly between the two CMC groups (triple negative and non triple negative), except for castration. In addition, we observed a correlation of this variable in the multivariate analysis with ST (471.42 ± 353.45 days). The behavior of the triple negative CMC seems to be less aggressive than in woman. The use of other molecular markers (Ki67, P53, P-caderina) must be used to distinguish the molecular subgroups in triple negative phenotype, and lead to the identification of more or less aggressive triple negative phenotypes. As similar CMC in general, castration may influence the occurrence of CMC triple negative.